Parent‐related mechanisms underlying the social gradient of childhood overweight and obesity: a systematic review. (18th June 2016) - Mech, P.; Hooley, M.; Skouteris, H.; Williams, J.
Abstract: Background: Low socio‐economic status (SES) is a significant risk factor for childhood overweight and obesity (COWOB) in high‐income countries. Parents to young children buffer and accentuate social and cultural influences, and are central to the development of this disease. An understanding of the parent‐related mechanisms that underlie the SES–COWOB relationship is needed to improve the efficacy of prevention and intervention efforts. Objective: A systematic review of relevant literature was conducted to investigate the mechanisms by which levels of SES (low, middle and high) are associated to COWOB, by exploring mediation and interaction effects. Method: Six electronic databases were searched yielding 5155 initial records, once duplicates were removed. Studies were included if they investigated COWOB, SES, parent‐related factors and the multivariate relationship between these factors. Thirty studies were included. Factors found to be mediating the SES–COWOB relationship or interacting with SES to influence COWOB were categorized according to an ecological systems framework, at child, parent, household and social system level factors. Results: High parent body mass index, ethnicity, child‐care attendance, high TV time (mother and child), breastfeeding (early weaning), food intake behaviours and birthweight potentially mediate the relationship between SES and COWOB. Different risk factors for COWOB in different SES groups were found. For low SES families, parental obesity and maternal depressive symptoms were strong risk factors for COWOB, whereas long maternal working hours and a permissive parenting style were risk factors for higher SES families. None of the studies investigated parental psychological attributes such as attitudes, beliefs, self‐esteem and so on as potential mechanisms/risk factors. Conclusions: Families from different SES groups have different risk and protective factors for COWOB. Prevention and intervention efforts may have improved efficacy if they are tailored to address specific risk factors within SES.